Effect of regular soccer training on morphological and motor characteristics of deaf girls aged 14–18 years: a comparative analysis - Adam Michał Szulc; Krzysztof Buśko (Scientific Reports)
Abstract The aim of this study was to evaluate body composition and the level of selected motor skills of the lower limbs in female participants, including 13 deaf students who are physically inactive (age 16.11 ± 1.53 years), 8 deaf soccer players (age 16.13 ± 1.25 years), and 16 hearing soccer players (age 16.41 ± 1.23 years). No significant differences were observed among the groups in terms of body weight, height, or measured perimeters. Regarding body composition, significant differences were identified between female soccer players and deaf physically inactive girls. Regular training appeared to result in similar 35-m sprint times among deaf and hearing female soccer players. A post-hoc analysis revealed no statistically significant differences between hearing and deaf female soccer players across most variables, except for peak torque relative to body mass during flexion at an angular velocity of 180°·s⁻1 and lower limb muscle force expressed relative to body mass in the counter-movement jump (CMJ) test. The isokinetic testing of the moment of force indicated that deaf girls (from both groups) produced higher values than hearing soccer players. Both groups of deaf participants achieved lower jump heights values but generated higher power in the akimbo counter-movement jump (ACMJ) and CMJ tests compared to hearing soccer players. The higher values observed in some biomechanical variables among deaf female soccer players, as well as deaf non-active female students, may be influenced not only by training experience but also by factors such as proprioception and musculoskeletal compensation.